Fusobacterium nucleatum as an oral bacteria promotes the carcinogenesis of laryngeal cancer via upregulating YWHAZ - Yiyue Ren; Jing Ye; Liuhong Shi; Kehao Le; Yifan Wang (Journal of Oral Microbiology)
Background and purpose F. nucleatum, a gram-negative oral bacteria, is abundant in laryngeal cancer (LC). While specific 14-3-3 proteins act as LC oncogenes, the link between F. nucleatum and 14-3-3 proteins dysregulation remains unknown.Materials and methods Transcriptome data from 520 HNSC patients were obtained from TCGA. DEGs were evaluated by Wilcoxon test, and survival analysis done by KM plotter. In 41 untreated LC patients, F. nucleatum was detected by PCR. GEO data assessed 14-3-3 protein changes post F. nucleatum infection, verified in HuLa-PC and LC cells (Tu686, LCC). YWHAZ oncogenic role was tested in vitro and in xenografts. YWHAZ knockdown confirmed F. nucleatum’s oncogenic effects are YWHAZ-dependent.Results F. nucleatum positive tumors have increased YWAHZ. F. nucleatum infection upregulates the expression of YWHAZ in HuLa-PC, Tu686 and Hep-2 cells. YWAHZ overexpression promotes proliferation, migration and colony formation but inhibits apoptosis of HuLa-PC and LCa cells via activating Akt signaling. F. nucleatum infection promotes the tumor growth. Knockdown YWAHZ in LCa cells totally rescued the phenotypes of F. nucleatum infection.Conclusions We identified for the first time that F. nucleatum infection promotes the development of LCa via upregulating YWHAZ, which provides a new clue for LCa treatment.